The Christian community and pastoral health care - Maritano, Livio (Medicina e Morale, 1990)
Because of its fundamental nature, the church turns its pastoral attention to all the spheres in which man lives and works. One of these is certainly the field of pastoral health care because it deals with the sick and the suffering. The author, who is a bishop, points out the urgent need for authenthic pastoral health care. This is especially necessary because of the condition of need in which the suffering find themselves. It is a situation which a mature Christian community ought to be able to deal with. The community should announce the particular vocation inherent in the diseased state to the Christian and assist him in his answer to the call. This was recently expressed in the "Public health pastoral in the church in Italy", edited by the CEI and the main points are covered by the author.